The Influence of Consumer Knowledge of Halal Supply Chain Practices on Purchase Intention in Halal Personal Care & Beauty Products - Adiningtyas, Yayang; Yunus, Erlinda (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: As a country with the largest Moslem population in the world, halal products are in demand in Indonesia, and manufacturers need to start implementing halal supply chain practices to ensure that their products meet the halal standards of Moslem communities. Consumer knowledge about the Halal Supply Chain is now more essential, ensuring product compliance with halal standards and religious integrity. Purpose: This research analyzes the influence of consumers' knowledge about the Halal Supply Chain (such as sourcing, production, handling and storage, logistics and packaging, and retailing) on purchase intention for personal care and beauty products. Design/methodology/approach: The research uses an explanatory quantitative approach through an online survey with instrument test analysis, and hypothesis testing using multiple linear regression. Data were collected using convenience sampling and the snowball approach. Findings/results: The results of statistical tests on 104 valid consumer data show that halal resourcing positively influences consumers' purchasing interest in personal care and beauty products. Meanwhile, there needs to be more evidence that other aspects, namely halal sourcing, production, handling and storage, logistics and packaging, and retailing, positively affect purchasing interest. Conclusion: Developing a halal supply chain will be one strategy for responding to market demands. This requires producers to carry out production, storage, and delivery in a halal manner or under Islamic law. This research shows that consumer knowledge about halal raw materials significantly affects their intention to purchase halal personal care and beauty products. Managers must ensure that information about halal raw materials is communicated to consumers because it will attract their buying interest. Further research could enrich the results of this study with data from companies’ perspectives. Originality/value (state of the art): This research highlights the importance of consumer knowledge of halal supply chain practices in influencing purchasing interest in halal personal care and beauty products. Consumer understanding regarding halal products and halal supply chain practices is key to understanding increasingly religious purchasing behavior in Indonesia. This research contributes to supply chain management literature in the field of Halal Supply Chain as well as to Indonesian companies in the personal care and beauty industry. Keywords: purchase intentions, halal logistics, halal resourcing, halal supply chain, personal care and beauty products